EFFECT OF EXHAUST FAN TO MICROORGANISM CONCENTRATION IN THE AIR-CONDITIONED ROOM - Adib, Moh; Sunarsieh; Salbiah Kastari (Malaysian Journal of Public Health Medicine, 2020)
Specific amounts of bacteria and fungi in the room can cause Sick Building Syndrome (SBS). The main reason for bacteria and fungi accumulation is a lack of air circulation in the air-conditioned room. Therefore, we study exhaust fan usage to microorganism concentration in the air-conditioned room. The objective of this study is to find the optimum exhaust fan running time for reducing microorganism concentration until below the threshold value. The quasi-experiment was using with repeated experiments and non-random methodology. The samples were consisting of four air-conditioned classrooms with six repeated measurements. The sampling instrument used a petri dish filled with NA (Nutrient Agar) and PDA (Potato Dextrose Agar) placed at five points in each room. The results showed that the variation of exhaust fan running time sig affected the concentration of bacteria (sig ~0) and fungi (sig 0.023) in the classrooms. We found that exhaust fan can reduce the bacteria concentration. Although we observed that the exhaust fan gives inconsistency effect to reduce the fungi concentration in the classrooms.